2005
DOI: 10.1007/s11194-005-4603-0
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone, Sexual Offense Recidivism, and Treatment Effect Among Adult Male Sex Offenders

Abstract: The relationship between serum testosterone and sexual violence was examined in a sample of 501 convicted adult male sex offenders attending an intensive in-hospital group psychotherapy treatment program. It was found that men with higher testosterone tended to have committed the most invasive sexual crimes (p < .001, two-tailed). Further, a positive partial correlation (controlling for age) between testosterone and sexual offense recidivism over a lengthy follow-up period (mean = 8.9 years) was found. When th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 40 publications
0
14
0
1
Order By: Relevance
“…Separating the group into patients who completed the therapy and those who discontinued it prematurely, the correlation remained significant only in the dropout group. Moreover, the portion of subjects with elevated T levels (e.g., higher than 29.9 nmol/L, corresponding to 8.6 ng/mL) was much higher in the completer group (11.9%) and in the drop-out group (12.1%) than in the healthy population (2.5%) [56]. In contrast, examining 10 sexual offenders and 10 healthy controls, Haake et al did not find different acute neuroendocrine responses to sexual stimulation based on sexually explicit videos and masturbation until orgasm even though sexual offenders were selected for high sexual drive combined with a short refractory period or high masturbation frequency or both [57].…”
Section: Endocrinology Of Paraphiliamentioning
confidence: 88%
See 1 more Smart Citation
“…Separating the group into patients who completed the therapy and those who discontinued it prematurely, the correlation remained significant only in the dropout group. Moreover, the portion of subjects with elevated T levels (e.g., higher than 29.9 nmol/L, corresponding to 8.6 ng/mL) was much higher in the completer group (11.9%) and in the drop-out group (12.1%) than in the healthy population (2.5%) [56]. In contrast, examining 10 sexual offenders and 10 healthy controls, Haake et al did not find different acute neuroendocrine responses to sexual stimulation based on sexually explicit videos and masturbation until orgasm even though sexual offenders were selected for high sexual drive combined with a short refractory period or high masturbation frequency or both [57].…”
Section: Endocrinology Of Paraphiliamentioning
confidence: 88%
“…In a sample of 501 convicted adult male sex offenders attending an intensive in-hospital group psychotherapy treatment program, it was found that men with higher T levels tended to have committed more physically abusive sexual crimes [56]. Adjusting for age, T level was partially positively correlated with sexual offense recidivism over a mean follow-up period of 8.9 years.…”
Section: Endocrinology Of Paraphiliamentioning
confidence: 96%
“…Another study advocated the hypothesis that T is related to the severity of expressed aggression, associated with sexual offending. The authors have concluded that serum T levels may predict sexual offense recidivism more precisely than that anticipated earlier (19). This suggests that T is not only related to aggression and sexual drive alone, but it may also be related to sexual aggression.…”
Section: Testosterone and Sexual Offendingmentioning
confidence: 91%
“…88 A more recent investigation examined serum testosterone levels in 501 adult male sex offenders. 89 Men with higher testosterone were reported to have historically committed the most invasive sex crimes and were reported to be more likely to recidivate.…”
Section: Physiologymentioning
confidence: 99%